2006
DOI: 10.1016/j.febslet.2006.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Nischarin as a functional imidazoline (I1) receptor

Abstract: Gene matching shows that Nischarin is a mouse homologue of human imidazoline receptor antisera-selective (IRAS) protein, a viable candidate of the imidazoline (I 1 ) receptor. Nischarin and IRAS share the functions of enhancing cell survival, growth and migration. Bioinformatics modeling indicates that the IRAS and Nischarin may be transmembrane proteins and the convergence information raises the interesting possibility that Nischarin might serve as the I 1 -receptor. To test this hypothesis, we developed anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 17 publications
2
39
1
1
Order By: Relevance
“…The IR-1 protein has been associated with IRAS (Li et al, 2006;Zhang & Abdel-Rahman, 2006), a membrane-linked protein without similarity to G-protein coupled receptors (Plletz et al, 2000). IRAS interacts with a number of membranous receptors, such as the mu-opioid receptor, of relevance to mood disorders Piletz et al, 2000a;Wu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The IR-1 protein has been associated with IRAS (Li et al, 2006;Zhang & Abdel-Rahman, 2006), a membrane-linked protein without similarity to G-protein coupled receptors (Plletz et al, 2000). IRAS interacts with a number of membranous receptors, such as the mu-opioid receptor, of relevance to mood disorders Piletz et al, 2000a;Wu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent findings in rat pheochromocytoma (PC12) cells (Zhang and Abdel-Rahman, 2006), supported by a subsequent study in the same cell line (Sun et al, 2007), suggest that nischarin serves as, or at least shares, a common signaling pathway with the I 1 R. Nischarin was first identified as a mouse homolog of human IRAS (Alahari et al, 2000;Alahari, 2003). It is noteworthy that human IRAS has been considered the I 1 R since the transfection of IRAS cDNA into the Chinese hamster ovary cells led to the expression of highaffinity I 1 binding sites for moxonidine and rilmenidine (Piletz et al, 2000).…”
mentioning
confidence: 99%
“…Similarly, PC12 cells transfected with cDNA encoding nischarin, increased I 1 R binding sites as shown by radioligand binding studies. Nischarin antisense abolished both expression of protein as well as substantially reduced the generation of ERK elicited by I 1 R agonist [27]. Molderings and colleagues conducted radioligand binding experiments with clonidine and moxonidine in PC12 cells and concluded that I 1 R represented a mixture of S1P1/S1P3-receptor hetero-dimers [20].…”
Section: Effects Of Nisch Sirna On Nischarin Protein Expression Erk mentioning
confidence: 99%
“…Similar to our findings, nischarin antisense oligodeoxynucleotide (ODN) abolished the expression of nischarin in PC12 cells. Moreover, nischarin ODN eliminated the phosphorylation of ERK1/2 elicited by another I 1 -imidazoline agonist, rilmenidine, in PC12 cells [27]. Additional experiments were done using lower concentrations of S43126 (10 -9 M) in combination with varying doses of insulin (10 -9 -10 -5 M) and also using insulin (10 -9 M) with varying doses of S43126 (10 -9 -10 -5 M).…”
Section: Effects Of Nisch Sirna On Nischarin Protein Expression Erk mentioning
confidence: 99%
See 1 more Smart Citation